Expression of Mouse Telomerase Catalytic Subunit mTERT Gene in Testis of SD Rats and Its Significance - 叶哲伟 陈晓春 杨述华 陈江 熊雅丽 鲁功成 (Current medical science, 2003)
To study the expression of mTERT gene in the testis of SD rats and its significance, in situ hybridization (ISH) techniques were used to detect the expression of telomerase gene mTERT mRNA in the testis of SD rats. The expression of mTERT was detectable in different-age male SD rats" testis. There was a positive correlation between the expression of mTERT and the location of germ cells (spermatogonia, spermatocyte, spermatid). In Sertoli cells, leydig cell and spermatozoa, telomerase mTERT was not detected. Type A spermatogonia expressed the highest level of telomerase mTERT mRNA. Our results suggest that the expression of mTERT gene in the testis of SD rats is of lifetime and coincide with the telomerase activity.